A phase 1 dose escalation study of the oncolytic adenovirus enadenotucirev, administered intravenously to patients with epithelial solid tumors (EVOLVE). Issue 1 (28th January 2019) - Machiels, Jean-Pascal; Salazar, Ramon; Rottey, Sylvie; Duran, Ignacio; Dirix, Luc; Geboes, Karen; Wilkinson-Blanc, Christine; Pover, Gillian; Alvis, Simon; Champion, Brian; Fisher, Kerry; McElwaine-Johnn, Hilary; et al.
Abstract : Background: Enadenotucirev is a chimeric adenovirus with demonstrated preclinical tumor-selective cytotoxicity and a short half-life. Further clinical mechanism of action data showed that enadenotucirev can gain access to and replicate within different types of epithelial tumors. This phase 1 dose escalation study assessed intravenous (IV) dose escalation with enadenotucirev to establish the maximum tolerated dose (MTD) and subsequently identify a suitable schedule for repeated cycles. Methods: Sixty-one patients with advanced epithelial tumors unresponsive to conventional therapy were enrolled and received enadenotucirev monotherapy as part of this study. During the phase 1a dose escalation ( n  = 22) and expansion ( n  = 9), delivery of enadenotucirev between 1 × 10 10 and 1 × 10 13 viral particles (vp) on days 1, 3, and 5 (single cycle) was used to determine an appropriate MTD. Subsequent treatment cohorts (phase 1a, n  = 6 and phase 1b, n  = 24) examined the feasibility of repeated dosing cycles in either 3-weekly or weekly dosing regimens. Results: Enadenotucirev displayed a predictable and manageable safety profile at doses up to the MTD of 3 × 10 12 vp, irrespective of infusion time or dosing schedule. The most commonly reported treatment-emergent adverse events (TEAEs) of grade 3 or higher were hypoxia, lymphopenia, and neutropenia. The frequency of all TEAEs (notably pyrexia and chills) was highest within 24 h of the first enadenotucirev infusion and decreased upon subsequent dosing. Additionally, delivery of three doses of enadenotucirev over 5 days optimized pharmacokinetic and chemokine profiles in the circulation over time. Conclusions: This study provides key clinical data in patients with solid epithelial tumors following treatment with IV enadenotucirev monotherapy and supports further investigation of enadenotucirev in combination with other therapeutic agents at doses up to the MTD of 3 × 10 12 vp. Trial registration: (ClinicalTrials.gov Identifier: NCT02028442 ). Trial registration date: 07 January 2014 – Retrospectively registered.